(Live!) The Post-traumatic Futurities of Black Debility - Koivisto, Mikko O. (Disability Studies Quarterly, 2019)
This article investigates the possibilities of artistic and performative strategies for elucidating forms of systemic violence targeted at racialized and disabled bodies. The analysis focuses on the album PTSD: Post traumatic stress disorder by the New York rapper Pharoahe Monch, delving into the ways in which it explores the intersections of Blackness and disability. The album's lyrics range from a critique of the structural racism in contemporary American society to subjective, embodied experiences of clinical depression, anxiety, and chronic asthma—and their complex entanglement. Informed by Jasbir Puar's formulation of 'debility' this article examines how Pharoahe Monch's album, as an expression and a performance of a singular life, helps to conceptualize the effects of the cultural and representational apparatuses that participate in marginalizing, devaluing, endangering, and annihilating Black and disabled lives.